HUBUNGAN BACKGROUND KELUARGA DENGAN SIKAP KELUARGA PADA KASUS RUJUKAN KEGAWATDARURATAN MATERNAL - Ina Indrati; Prawasti Rahayuningtyas Andrio; Iznih Rahmi Lessy (LPPM Universitas Abdurrab, 2024)
Maternal emergencies can occur during pregnancy, childbirth, and the postpartum period, if not treated immediately, it can cause maternal and fetal death. Maternal neonatal emergencies can be prevented if first aid is provided for obstetric emergencies in mothers and babies. It also depends on the family's attitude in responding to this event. Family background includes age, knowledge and economic support/employment is one of the supporters of family attitudes in referring emergencies. The purpose of this study was to determine the correlation between family background and family attitudes in cases of emergency for pregnant women. This correlational research design with a cross sectional approach has a population of all family members of pregnant women at TPMB Kartini during November 2023 to April 2024. This research uses accidental sampling on pregnant women experiencing emergencies in the last 6 months, the sample obtained is 30 respondents. The instrument in the study was given to family members to fill out a questionnaire provided by the researcher. Data analysis of this study used gamma and somers'd correlation tests. The results of this study obtained a P value in the age category with an attitude of p = 0.003 r = 0.6; in the education category with an attitude of p = 0.01 r = 0.42 and in the employment category with an attitude of p = 0.001 r = 0.82. It can be concluded that there is a relationship between family background (age, education and occupation) and attitude in cases of referral of maternal emergencies. Further research is recommended to analyze the delay in referral of emergencies as a source of reference for anticipatory measures of maternal and fetal mortality